A New Approach on Increasing the Heat Transfer Performance of Self Helical Finned Tubes - Özel, Cihan; Macit, Cevher Kürşat; Taşkıran, Ali; Özel, Meral (Fırat University, 2022)
In this study, in order to increase the heat transfer performance of self-helical finned pipes, the wall thickness of the pipe was thinned and the fin height was increased. For this purpose, a standard pipe with a wall thickness of 3 mm was chosen initially, and the wall thickness of the pipe was recalculated with the pipe strength relation, taking into account the material and operating conditions of this pipe. As a result of the calculation, the pipe wall thickness was found to be 1.077 mm and this value was seen to be thinner than the standard selected pipe wall thickness (3 mm). With such an application, the wall thickness of the pipe was reduced, while the fin height of 5 mm, which was initially selected for the standard pipe, was increased to 6,923 mm. Later, both pipes were designed in Solidwork environment with pitches of 10, 20 and 30 mm. The thermal performances of the designed pipes were examined using different Reynolds (Re) numbers (5000, 10000 and 15000) in Ansys Fluent environment. According to the results of this analysis, the best performance in terms of heat transfer was obtained in the pipe with 5000 Re value and a wall thickness of 1.077 mm.

Bu çalışmada, kendinden helisel kanatlı boruların ısı transfer performanslarını artırmak için borunun cidar kalınlığı inceltilerek kanat yüksekliğini artırma uygulamasına gidildi. Bu amaç için başlangıçta 3 mm et kalınlığına sahip standart bir boru seçildi ve bu borunun malzemesi ve çalışma koşulları dikkate alınarak boru mukavemet bağıntısı ile borunun et kalınlığı yeniden hesaplandı. Hesaplama sonucunda boru et kalınlığı 1,077 mm olarak bulundu ve bu değerin standart olarak seçilen boru et kalınlığından (3 mm) daha ince olduğu görüldü. Bu şekilde bir uygulama ile boru cidar kalınlığı azalırken başlangıçta standart boru için seçilen 5 mm’ lik kanat yüksekliğinin ise 6,923 mm ye artırılması sağlandı. Daha sonra her iki boru 10, 20 ve 30 mm’ lik hatvelerde Solidwork ortamında tasarlandı. Tasarımları yapılan boruların ısıl performansları ise Ansys Fluent ortamında farklı Reynolds (Re) sayıları (5000, 10000 ve 15000) kullanılarak incelendi. Bu analiz sonuçlarına göre ısı transferi açısından en iyi performans 5000 Re değerinde ve cidar kalınlığı 1,077 mm olan boruda elde edildi.
Kendinden Helisel Kanatlı Boruların Isı Transfer Performansını Artırmaya Yönelik Yeni Bir Yaklaşım